Perbandingan Motivasi Belajar Siswa Pada Saat Pembelajaran IPS Secara Daring dan Tatap Muka: Studi Komparatif di SMPN 1 Lembang - Mirma Lutfiatunnisa (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2023)
The outbreak of Covid-19 has significantly impacted students’ learning process and motivation levels. This study aimed to investigate students' motivation levels during face-to-face and virtual learning in social studies and compare students’ learning motivation after the policies implemented due to Covid-19. The research employed a quantitative approach with a comparative descriptive method, with a sample size of 72 students from classes VII-A and VII-B of SMPN 1 Lembang. The instrument testing was conducted by performing validity and reliability tests with a significance table of 5%. The data obtained were processed using normality tests, which showed that the data was normal and homogeneous. The data was processed through parametric testing by performing independent samples t-test. The statistical test results showed a significance value of 0.000, less than 0.05. The statistical test results concluded that there were differences in students' motivation when learning social studies in virtual and face-to-face settings. The findings of this study revealed that the difference in motivation level could be observed from the average descriptive analysis of students during virtual social studies learning in the low and high categories, while face-to-face learning was in the high and very high categories between male and female students.